System Dynamics Modelling of Population Growth and Waste Management Landfill Capacity Sustainability in Palangka Raya - Petrisly Perkasa; Wiratno Y Sigin; Ni Putu Diah Agustin Permanasuri; Yusuf Aguswan; Airways Parlindungan Siahaan; Riska Ovany (Gema Lingkungan Kesehatan, 2026)
This study analyzes the growing challenges of municipal solid waste management in Palangka Raya, driven by rapid population growth and limited landfill capacity. The research aims to develop an integrated dynamic system model combining population dynamics and waste management performance to project future conditions and evaluate policy interventions. Using a system dynamics approach, the study models population growth, household waste generation, landfill accumulation, and waste reduction strategies. Primary data were collected through field measurements of existing waste volumes and landfill capacities, while secondary data were obtained from official statistics and relevant reports. Model validation demonstrates high accuracy in projecting population growth, a key driver of increasing waste generation. Simulation results indicate that, under the current conditions, the Bukit Tunggal landfill will reach overload in 2018, revealing an unsustainable system. Moderate interventions produce minimal improvement, while an optimistic scenario delays landfill overload only until 2026. The findings demonstrate that achieving long-term landfill sustainability requires an extreme waste reduction strategy of at least 85% through significant enhancement of recycling, composting, and waste diversion efforts. The study concludes that incremental policies are inadequate to address the worsening waste crisis. Instead, a transformative shift toward high-performance waste processing and decisive policy intervention is essential to maintain landfill functionality and support sustainable urban development. The integrated model developed in this research provides a valuable tool for policymakers to design effective and long-term waste management strategies.